Caprine nictitating membrane cell culture for production of small ruminants lentivirus antigen - de Azevedo, Dalva Alana Aragão; Araújo, Juscilânia Furtado; de Sousa, Ana Lídia Madeira; Dias, Ronaldo Pereira; de Souza, Thiago Sampaio; Andrioli, Alice; Pinheiro, Raymundo Rizaldo (Brazilian Journal of Veterinary Medicine, 2015)
ABSTRACT. Azevedo D.A.A., Araújo J.F., Sousa A.L.M. de, Dias R.P., Souza T.S. de, Andrioli A. & Pinheiro R.R. [Caprine nictitating membrane cell culture for production of small ruminants lentivirus antigen.] Produção de antí- geno de lentivírus de pequenos ruminantes através da cultura celular de membrana nictitante caprina. Revista Brasileira de Medicina Veterinária, 37(4):316-320, 2015. Empresa Brasileira de Pesquisa Agropecuária (Embrapa Caprinos e Ovinos), Fazenda Três Lagoas, Estrada Sobral/Jordão Km 4, Sobral, CE 62010-970, Brasil. E-mail: dalvaazevedo@outlook.com Small Ruminants lentivirus (SRLV) belong to the Retroviridae family and is the etiologic agent of caprine arthritis encephalitis in goats and maedi-visna in sheep. Cells of the monocytic-phagocytic lineage are the main viral targets and infected hosts cannot develop a curative immune response. We evaluated whether nictitating membrane (NM) cells can be cultivated in vitro and also whether it is a feasible system for SRLV antigen production for immunodiagnosis purposes. MN cells were collected from a SRLV negative animal and cultivated in minimal essential media supplemented with bovine fetal serum. Subcultures were inoculated with caprine arthritis encephalitis virus (CAEV) Cork strain, the supernatant was collected, clarified by centrifugation (3.400 g for 20 minutes), concentrated using the AMICON® system. Samples were subjected to agar gel immunodiffusion (AGID) tests. MN cells presented satisfactory performance, were amenable to several subcultivation.